2016
DOI: 10.1016/j.nanoen.2016.01.026
|View full text |Cite
|
Sign up to set email alerts
|

Thermally conductive separator with hierarchical nano/microstructures for improving thermal management of batteries

Abstract: Thermal management is critical to improving battery performance and suppressing thermal runaway. Besides developing external cooling technologies, it is important to understand and control thermal transport inside batteries. In this paper, heat transfer inside batteries is first analyzed and the thermal conductivity of each component is measured. The results show that low thermal conductivity of the separator is one major barrier for heat transfer in Li-ion batteries. To improve thermal conductivity of the sep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
56
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 81 publications
(56 citation statements)
references
References 27 publications
0
56
0
Order By: Relevance
“…Thermal property measurements are primarily done either at material level or at the cell level in Li-ion cells. At material level, the thermal property measurements of electrodes [45][46][47][48][49], electrolyte [50], separator [51,52], electrode stack [46,53], and contact thermal resistance [54,55] have been reported. Such material-level measurements are key in understanding the heat transfer inside a Li-ion cell and in determining the rate-limiting heat transfer processes.…”
Section: Thermal Propertymentioning
confidence: 99%
See 2 more Smart Citations
“…Thermal property measurements are primarily done either at material level or at the cell level in Li-ion cells. At material level, the thermal property measurements of electrodes [45][46][47][48][49], electrolyte [50], separator [51,52], electrode stack [46,53], and contact thermal resistance [54,55] have been reported. Such material-level measurements are key in understanding the heat transfer inside a Li-ion cell and in determining the rate-limiting heat transfer processes.…”
Section: Thermal Propertymentioning
confidence: 99%
“…Cross-plane thermal conductivity of electrodes and separators has been measured using a differential steady-state method [52]. The experimental setup is very similar to that of the 1D heat flowmeter previously used [45].…”
Section: Thermal Propertymentioning
confidence: 99%
See 1 more Smart Citation
“…Yang et al measured and identified that the separator is a major limiting factor for heat dissipation in liquid state LIBs, therefore a hierarchical polymer separator was prepared to obtain higher thermal conductivity. 12 A novel system that incorporates phase-change material was proposed to store and utilize the heat generated inside LIBs. 13 However, thermal transport inside SSLIBs is less investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Rechargeable Li‐ion batteries are critical to various applications, such as portable electronics, vehicle electrification and grid‐level energy storage . However, Li‐ion batteries have low thermal stability and can explode when they are exposed to abusive conditions such as mechanical deformation, short circuit, over‐charging and external heating . Such instability originates from the high flammability of organic electrolyte and becomes more severe upon the pursuit of batteries with high energy density .…”
Section: Introductionmentioning
confidence: 99%